Analisis Cost of Illness Pasien Covid-19 di Rumah Sakit Jiwa Dr. Soeharto Heerdjan Jakarta Barat - Sherly Tandi Arrang; Irene Fira Rosa; Dion Notario (JFIOnline | Print ISSN 1412-1107 | e-ISSN 2355-696X, 2026)
COVID-19 (Coronavirus Disease 2019) is a new case that was reported to have occurred in 2019 in China (Wuhan) and the first case in Indonesia in March 2020. The high increase in cases requiring treatment related to patient care causes an economic burden. Therefore, it is necessary to analyze the economic burden. The analysis uses the Cost of Illness (COI) method. This retrospective research was conducted based on data at RSJ Dr. Suharto Heerdjan for the period December 2020 - July 2021 by calculating the direct medical costs of patients. The analytical method used is Multiple Linear Regression ANOVA using the RStudio application. The number of respondents was 138 patients. In the results of the analysis, it was found that the average total direct medical costs of COVID-19 inpatients based on age was Rp. 6,580,657 (0-5 years), Rp. 8,317,592 (6-18 years), Rp. 8,595,254 (19-30 years old), Rp. 11,787,268 (31-45 years), Rp. 12,537,695 (46-59 years old), and Rp. 16,250,460 (>60 years). Based on gender Rp. 12,416,202 (women) and Rp. 11,285,017 (male). Based on the length of stay, Rp. 7,881,911 (<7 days), Rp. 12,721,150 (7-14 days), and Rp. 26,282,724 (>14 days). Based on the level of severity, Rp. 10,096,730 (mild), Rp. 10,633,881 (medium), and Rp. 16,597,570 (severe). Based on comorbid disease, Rp. 16,981,774 (without comorbid), Rp. 19,670,640 (1 comorbid), Rp. 22,990,759 (2 comorbid), and Rp. 30,231,603 (>2 comorbid). There was a significant effect between length of stay, severity, and comorbid disease on direct medical costs (P<0.05), while there was no significant effect between age and gender on direct medical costs for inpatient care (P>0.05).